Relationships of Late Pleistocene giant deer as revealed by Sinomegaceros mitogenomes from East Asia - Bo Xiao; Alba Rey-lglesia; Junxia Yuan; Jiaming Hu; Shiwen Song; Yamei Hou; Xi Chen; Mietje Germonpré; Lei Bao; Siren Wang; Taogetongqimuge; Lbova Liudmila Valentinovna; et al. (iScience, 2023)
Summary: The giant deer, widespread in northern Eurasia during the Late Pleistocene, have been classified as western Megaloceros and eastern Sinomegaceros through morphological studies. While Megaloceros’s evolutionary history has been unveiled through mitogenomes, Sinomegaceros remains molecularly unexplored. Herein, we generated mitogenomes of giant deer from East Asia. We find that, in contrast to the morphological differences between Megaloceros and Sinomegaceros, they are mixed in the mitochondrial phylogeny, and Siberian specimens suggest a range contact or overlap between these two groups. Meanwhile, one deep divergent clade and another surviving until 20.1 thousand years ago (ka) were detected in northeastern China, the latter implying this area as a potential refugium during the Last Glacial Maximum (LGM). Moreover, stable isotope analyses indicate correlations between climate-introduced vegetation changes and giant deer extinction. Our study demonstrates the genetic relationship between eastern and western giant deer and explores the promoters of their extirpation in northern East Asia.